A prediction model for secondary invasive fungal infection among severe SARS-CoV-2 positive patients in ICU - Su, Leilei; Yu, Tong; Zhang, Chunmei; Huo, Pengfei; Zhao, Zhongyan (Frontiers in Cellular and Infection Microbiology, 2024)
Background: The global COVID-19 pandemic has resulted in over seven million deaths, and IFI can further complicate the clinical course of COVID-19. Coinfection of COVID-19 and IFI (secondary IFI) pose significant threats not only to healthcare systems but also to patient lives. After the control measures for COVID-19 were lifted in China, we observed a substantial number of ICU patients developing COVID-19-associated IFI. This creates an urgent need for predictive assessment of COVID-19 patients in the ICU environment for early detection of suspected fungal infection cases.Methods: This study is a single-center, retrospective research endeavor. We conducted a casecontrol study on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive patients.The cases consisted of patients who developed any secondary IFI during their ICU stay at